2016
DOI: 10.1002/bkcs.10842
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and Sensitive Determination of Benzalkonium Chloride Biocide Residues in Soil Using Liquid Chromatography–Tandem Mass Spectrometry after Ultrasonically Assisted Extraction

Abstract: The trace level determination of five benzalkonium chloride (BAC) compounds in soil was investigated using ion‐pairing liquid chromatography–tandem mass spectrometry. The instrumental intensities of the target compounds were compared with four ion‐pairing reagents, and 30 mM perfluoroheptanoic acid (PFHA) was selected as the best reagent. An ultrasonically assisted extraction method was developed for soil. The optimum extraction conditions were as follows: extraction solvent, 30 mM PFHA in an acetone:acetonitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Acidified MeOH [ 15 , 16 , 19 , 21 ] and AcN [ 22 , 23 ] are the most commonly used solvents for the QAAC extraction of sludges, water and sediments. In our extraction trials we found that AcN with HCl worked best for soils ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Acidified MeOH [ 15 , 16 , 19 , 21 ] and AcN [ 22 , 23 ] are the most commonly used solvents for the QAAC extraction of sludges, water and sediments. In our extraction trials we found that AcN with HCl worked best for soils ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…High-performance liquid chromatography (HPLC) is used for separating BAC components, but the separation efficiency of the chromatographic column makes it challenging to completely separate the three components of BAC from the real sample matrix, making it unsuitable for simultaneously detecting multiple quaternary ammonium components in compound chemical disinfectant. Reverse-phase ion-pair HPLC using ion-pair reagents can alter the column efficiency and has a long equilibration time [ 20 ]. Furthermore, the unfavorable strong adsorption capacity of long-chain BAC can lead to peak tailing, affecting the integration of peaks for quantitative analysis [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers predicted that the concentration of QACs entering the soil through the application of organic fertilizers was about 3.5 mg/kg ( Mulder et al., 2018 ). Moreover, up to 28.5 mg/kg of benzalkonium chlorides (BACs) were still detected in soils in one region of South Korea for 6 months after the application of disinfectants containing BACs ( Kang and Shin, 2016 ). Besides, QACs were detected in some farmland soils at concentrations as high as 0.82 mg/kg due to irrigation with QACs-tainted wastewater ( Jardak et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%